Who are the Māori "in-between"? Indigenous diversity and inequity across descent, ethnicity and Iwi knowledge. Issue 1 (2nd January 2023) - Greaves, Lara M.; Lindsay Latimer, Cinnamon; Li, Eileen; Hamley, Logan; Renfrew, Larissa; Sporle, Andrew; Milne, Barry
ABSTRACT: Policies increasingly reinforce the self-determination of Indigenous peoples, but issues remain around group definitions. Colonization has led to (de)identification with Māori (New Zealand's Indigenous peoples) identity markers. We explore differences between Māori on combinations of descent, ethnicity and Iwi (extended kinship group) knowledge in the 2013 Census, and self-reported discrimination. There were six groups within the Māori descent population: two did not know their Iwi – some identified solely as Māori ethnicity (2.8 per cent) – or Māori plus another ethnicity(-ies; 6.8 per cent); two did not identify as Māori ethnicity: more named their Iwi (7.2 per cent), than not (6.9 per cent); the largest groups knew their Iwi and identified as Māori ethnicity, either solely (30.8 per cent), or alongside another ethnicity(-ies; 34.3 per cent). We found a pattern of differences across demographics and discrimination, highlighting the complexity of Māori identity and the need to account for differences within Indigenous groups.